Depressive symptoms’ functional analysis in major depressive disorder - Gazzoni, Ana Paula (2021)
Major Depressive Disorder (MDD) causes impairment in all areas of the individual's life, and it will be a more disabling disease by the year 2020 according to the World Health Organization. The objective was to propose an understanding of the depressive symptoms of MDD present in DSM-5 from the perspective of behavior analysis (BA). The depressive symptoms of MDD were mainly due to aversive stimulation, negative reinforcement (avoidance a fugue behaviors), extinction and low positive reinforcement of non-depressive behaviors. A functional analysis of the relationship between the organism and the environment is needed to evaluate depressive symptoms. Relational and cultural factors (e. g., family and social), sex/gender, verbal behavior, and cultural practices must be considered in order to understand variability of depressive symptoms in MDD.Major Depressive Disorder (MDD) causes impairment in all areas of the individual's life, and it will be a more disabling disease by the year 2020 according to the World Health Organization. The objective was to propose an understanding of the depressive symptoms of MDD present in DSM-5 from the perspective of behavior analysis (BA). The depressive symptoms of MDD were mainly due to aversive stimulation, negative reinforcement (avoidance a fugue behaviors), extinction and low positive reinforcement of non-depressive behaviors. A functional analysis of the relationship between the organism and the environment is needed to evaluate depressive symptoms. Relational and cultural factors (e. g., family and social), sex/gender, verbal behavior, and cultural practices must be considered in order to understand variability of depressive symptoms in MDD.